Business Information Systems Workshops - Meersman, Davor; Debruyne, C. (Springer, 2011)
We discuss a semantic platform that matches a customer’s purchase intent against vendor offers. The customers’ perception on particular products, including evolving needs and preferences, were captured in a request and product ontology, in turn used to annotate vendor offers. During the project, however, we observed an important gap between the intent descriptions of users and the available data in product descriptions. We argue that through the inclusion of peripheral data, vendors are able to innovate according to customer preference, and users receive increasingly relevant results. We present a method that is essentially a customer-driven innovation system using product innovation ontologies.